Cobalt nanoparticles encapsulated in carbon nanotube-grafted nitrogen and sulfur co-doped multichannel carbon fibers as efficient bifunctional oxygen electrocatalysts. Issue 10 (16th February 2017) - Wang, Zhe; Peng, Shengjie; Hu, Yuxiang; Li, Linlin; Yan, Tao; Yang, Guorui; Ji, Dongxiao; Srinivasan, Madhavi; Pan, Zhijuan; Ramakrishna, Seeram
Abstract : Flexible metallic cobalt decorated CNT-grafted multichannel carbon fibers, co-doped with nitrogen and sulfur, exhibit excellent ORR and OER activities. Abstract : Developing flexible, efficient, and cost-effective electrocatalysts for the oxygen reduction reaction (ORR) and the oxygen evolution reaction (OER) is of paramount importance for designing fuel cells, metal–air batteries and water splitting units. Herein we present an economical approach for the synthesis of self-standing cobalt nanoparticles (NPs) anchored on carbon nanotube-grafted multichannel carbon fibers, co-doped with nitrogen and sulfur (Co@NS/CNT-MCFs), which exhibit comparable ORR (OER) activity to that of commercial Pt/C (RuO2 ) catalysts in terms of a half-wave potential of 0.837 V for the ORR, and a mere 362 mV overpotential at a current density of 10 mA cm −2 for the OER, as well as remarkable stability in an alkaline medium. The excellent electrocatalytic properties can be attributed to the hierarchically porous network structure and multiple heteroatom dopants introduced, which favor efficient reagent/product mass transport, in addition to providing a great number of active sites. As a proof of concept, the designed flexible catalysts are also employed as air cathodes in an assembled lithium–oxygen (Li–O2 ) cell with high specific capacity and outstanding operational durability. These results demonstrate the potential of this novel approach in developing suitable catalysts to enable the next generation of metal–air batteries.